2015
DOI: 10.3390/ijms16011312
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing in Females with Autism Implicates Novel and Candidate Genes

Abstract: Classical autism or autistic disorder belongs to a group of genetically heterogeneous conditions known as Autism Spectrum Disorders (ASD). Heritability is estimated as high as 90% for ASD with a recently reported compilation of 629 clinically relevant candidate and known genes. We chose to undertake a descriptive next generation whole exome sequencing case study of 30 well-characterized Caucasian females with autism (average age, 7.7 ± 2.6 years; age range, 5 to 16 years) from multiplex families. Genomic DNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 108 publications
2
72
0
3
Order By: Relevance
“…FIHT was reportedly included in recurrent CNVs in ASD [26]. Compound heterozygote deletion of CTNNA3 was reported in ASD patients [27] and a possible association of hemizygote deletion/mutation with ASD was proposed [27,28]. In ASD, the inability to engage in a flow of either verbal or non-verbal interaction has been described as social timing difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…FIHT was reportedly included in recurrent CNVs in ASD [26]. Compound heterozygote deletion of CTNNA3 was reported in ASD patients [27] and a possible association of hemizygote deletion/mutation with ASD was proposed [27,28]. In ASD, the inability to engage in a flow of either verbal or non-verbal interaction has been described as social timing difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits arising during the period of synapse formation [143], mutations and copy number variants found in genes encoding synaptic proteins [144-146], and perturbed dendritic spines observed in both post-mortem brains of ASD patients and in ASD mouse models [147-149] all point to ASD as a disorder of synapses. Multiplex families and twin studies have shown that ASDs have a heritability as high as 90% [143,150,151]. This has led to a large number of genomic studies searching for the molecular etiology of ASD, which together have proposed 695 candidate genes [152] among them PCDH8, PCDHGA1, PCDHB15 [150], PCDH9 [146,153], PCDH10 [153,154], PCDH15 [155] , PCDHB4 [156], and the PCDHA gene cluster [157].…”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
“…Multiplex families and twin studies have shown that ASDs have a heritability as high as 90% [143,150,151]. This has led to a large number of genomic studies searching for the molecular etiology of ASD, which together have proposed 695 candidate genes [152] among them PCDH8, PCDHGA1, PCDHB15 [150], PCDH9 [146,153], PCDH10 [153,154], PCDH15 [155] , PCDHB4 [156], and the PCDHA gene cluster [157]. …”
Section: Roles In Behavior and Neurological Or Neurodevelopmental Dismentioning
confidence: 99%
“…Consistently, genes co-expressed with stx shown in COXPRESdb (Okamura et al, 2015) are clustered into pathways in cancer as well as Notch and MAPK signaling pathways. Very recently, Stx mutations were found in patients with autism spectrum disorders (ASD) by whole-exome sequencing (Butler et al, 2015). Given the strong connection between PcG and ASD (Gao et al, 2014;Kumari and Usdin, 2014), Stx may play a role in ASD through its regulation of PcG activity.…”
Section: Regulated Protein Degradation Plays a General Role In Modulamentioning
confidence: 99%